2017
DOI: 10.1136/bmjopen-2016-012586
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changes in pill appearance in the adherence to angiotensin receptor blockers and in the blood pressure levels: a retrospective cohort study

Abstract: ObjectiveTo assess the level of adherence to angiotensin receptor blockers (ARBs) in patients regularly attending a community pharmacy and the influence of a change in patients' adherence to pharmacological treatment.DesignRetrospective cohort study of a random sample of consecutive patients collecting their medication.Setting40 community pharmacies in Alicante (Southeast Spain).Participants602 consecutive ≥18 years old patients following treatment with ARBs at least 3 previous refills were included.Main outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…In addition, in the multiple linear regression model, the cost (pNP, GAD) was associated with generic pregabalin, non-adherence (persistence/MPR) and lower clinical effectiveness. The temporal relationship between nonadherence, lower clinical effectiveness and greater healthcare resource utilization seems consistent in the literature reviewed [18,19,32,39].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In addition, in the multiple linear regression model, the cost (pNP, GAD) was associated with generic pregabalin, non-adherence (persistence/MPR) and lower clinical effectiveness. The temporal relationship between nonadherence, lower clinical effectiveness and greater healthcare resource utilization seems consistent in the literature reviewed [18,19,32,39].…”
Section: Discussionsupporting
confidence: 56%
“…In recent published studies, Lumbreras found that switching between pills of different appearances was associated with lower patient adherence to pharmacological treatment and a higher uncontrolled blood pressure than no change in pharmacological treatment or change only in package but not in pill appearance [19]. Cheng showed that higher suicide rates were reported in patients who used generic versus brand-name medicinal products [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This potential confusion may lead to medication errors, which could in turn lead to treatment non-adherence, cause a possible decrease in clinical effectiveness, trigger the onset of adverse effects and generate a potential increase in associated healthcare costs [ 18 20 ]. The change in pill appearance (physical characteristics of shape, color, size and packaging that identify medicines) which occurs when generic drugs are supplied by different brands over time might result in higher levels of treatment discontinuation or mean that patients are less likely to adhere to treatment [ 19 ]. Therefore, administration of a generic drug could be considered a factor to be taken into account, particularly in some countries, like Spain, where generic substitution is allowed and their governments encourage doctors to prescribe them.…”
Section: Introductionmentioning
confidence: 99%